2021
DOI: 10.1364/ol.431054
|View full text |Cite
|
Sign up to set email alerts
|

High-entropy chaos generation using semiconductor lasers subject to intensity-modulated optical injection for certified physical random number generation

Abstract: This study investigates high-entropy chaos generation using a semiconductor laser subject to intensity-modulated optical injection for certified physical random number generation. Chaos with a continuous spectral profile that is not only widely distributed but also broadly flattened over a bandwidth of 33 GHz is generated. The former suggests that the chaos can be sampled at a high rate while keeping sufficient un-correlation between data samples, and the latter indicates that the chaos possesses high entropy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…By continuing to increase the coupling strength so that (ξ s 12 , f i ) = (0.05, −20 GHz), as Figure 2(a-iv) shows, a broad and continuous spectral distribution appears for either laser, which is a typical signature of chaos. After photodetection, as Figure 2(b-iv) presents, such a spectral feature generates a broadband chaotic microwave with a spectral distribution of more than 40 GHz, which is highly advantageous for chaos-based applications, such as highresolution chaotic radars [39][40][41][42], high-speed chaotic communication [43][44][45][46], and highentropy random number generation [47][48][49][50]. Owing to the round-trip delay coupling, spectral components that are equally separated by 12.45 MHz, as those shown in the inset of Figure 2(b-i) yet with much weaker intensity, also emerge on top of the spectral distribution in Figure 2(b-iv).…”
Section: Dynamics Behaviors Under Symmetric Coupling Strengthmentioning
confidence: 99%
“…By continuing to increase the coupling strength so that (ξ s 12 , f i ) = (0.05, −20 GHz), as Figure 2(a-iv) shows, a broad and continuous spectral distribution appears for either laser, which is a typical signature of chaos. After photodetection, as Figure 2(b-iv) presents, such a spectral feature generates a broadband chaotic microwave with a spectral distribution of more than 40 GHz, which is highly advantageous for chaos-based applications, such as highresolution chaotic radars [39][40][41][42], high-speed chaotic communication [43][44][45][46], and highentropy random number generation [47][48][49][50]. Owing to the round-trip delay coupling, spectral components that are equally separated by 12.45 MHz, as those shown in the inset of Figure 2(b-i) yet with much weaker intensity, also emerge on top of the spectral distribution in Figure 2(b-iv).…”
Section: Dynamics Behaviors Under Symmetric Coupling Strengthmentioning
confidence: 99%
“…Optical chaos is one of the many dynamic characteristics of lasers. It is widely used in optical communication 1,2 , laser radar 3,4 , physical random number generation 5,6 , reservoir computing 7 and other fields. However, there are two problems in the practical application of laser chaotic signal.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9], brain inspired photon neuromorphic computing [10,11]. Semiconductor laser can exhibit rich dynamic characteristics through optical injection, optical feedback and photoelectric feedback [12][13][14][15][16], and laser chaos is one of the dynamic characteristics of laser that has been widely studied by scholars. In recent years, with the scholar further study of laser chaos, it is found that the output energy of laser is mainly concentrated around the relaxation oscillation frequency.…”
Section: Introductionmentioning
confidence: 99%